Kegiatan Bakti Sosial Pembagian Sembako Kepada Masyarakat Korban Bencana Banjir Bandang - Ayuni, Dini Qurrata; Parlindungan S, Gokma Toni; Safardi, Safardi; Bur, Suhatri; Untari, Puthi Dwi (Universitas Sumatera Barat, 2024)
It is hoped that this Community Service will have a positive effect, especially for the residents of Nagari Batang Salasih who were also affected by the Badang flood disaster. This paper aims to respond to the condition of the community's burden of lack of living necessities after the disaster. Seeing that economic activity is not yet normal, Unisbar Peduli is holding social service activities by distributing basic food packages to people in need. The community service method is carried out using a participatory approach by directly involving lecturers and students to directly distribute 150 basic food packages in Nagari Batang Salasih, Agam district, which is carried out in one day. The distribution or distribution of basic food packages runs smoothly and safely. It is hoped that this social service can ease the needs of the people who are directly affected by the Badang flood situation. This community service activity is fully supported by the Chancellor, lecturers and students so that the distribution of basic food packages can be carried out well